2013
DOI: 10.1097/fbp.0b013e3283618b16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional relationship between mouse hippocampal cholinergic and nitrergic systems in anxiogenic-like behavior

Abstract: Although a body of evidence shows the crucial role of hippocampal nitrergic and cholinergic systems in the modulation of anxiety, little is known about their functional relationship with regard to anxiety. The present study investigated the relationship between intra-CA1 administration of a nicotinic acetylcholine receptor antagonist (mecamylamine) and a nitric oxide synthase inhibitor [Nω-nitro-L-arginine methyl ester (L-NAME)] or its precursor (L-arginine) in anxiety-related behaviors. Mice received bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Indeed, hph mice in this study displayed ∼75% lower plasma nitrite and nitrate concentrations, an index of NO production, compared to WT mice, which is in line with other studies showing markedly reduced NO levels in hph-1 mice (Barker et al, 1998;Lam et al, 2007). In the elevated plus maze test (EPM, the precurser to the EZM), neuronal NO synthase knock-out mice displayed increased anxiety-like behaviours (Weitzdoerfer et al, 2004), and studies in both rats and mice have reported anxiogenic-like effects of NOS inhibitors in the EPM Vale et al, 1998;Zarrindast et al, 2013). While this could indicate that the increased anxiety-like behaviour observed in hph mice is linked to low NO levels, other studies have shown anxiolytic-like properties of NOS inhibitors (Guimarães et al, 1994;Volke et al, 1995;Faria et al, 1997;Spiacci et al, 2008).…”
Section: Phenotype Of Hph Mice In the Ezm And Mbsupporting
confidence: 71%
“…Indeed, hph mice in this study displayed ∼75% lower plasma nitrite and nitrate concentrations, an index of NO production, compared to WT mice, which is in line with other studies showing markedly reduced NO levels in hph-1 mice (Barker et al, 1998;Lam et al, 2007). In the elevated plus maze test (EPM, the precurser to the EZM), neuronal NO synthase knock-out mice displayed increased anxiety-like behaviours (Weitzdoerfer et al, 2004), and studies in both rats and mice have reported anxiogenic-like effects of NOS inhibitors in the EPM Vale et al, 1998;Zarrindast et al, 2013). While this could indicate that the increased anxiety-like behaviour observed in hph mice is linked to low NO levels, other studies have shown anxiolytic-like properties of NOS inhibitors (Guimarães et al, 1994;Volke et al, 1995;Faria et al, 1997;Spiacci et al, 2008).…”
Section: Phenotype Of Hph Mice In the Ezm And Mbsupporting
confidence: 71%